Quality Dimensions of Purchase Behavior Decision on Fishery Products - Nurliza Nurliza; Eva Dolorosa (Jurnal Manajemen & Agribisnis, 2017)
The role of fishery product has been developed and acknowledged in terms of food security both as income sources and food supplies for developing countries. On the other hand, quality control has become a challenge in overcoming consumers’ decision to purchase the products. The objective of research is to understand and evaluate consumer behavior in purchasing the products in regards to quality dimension on fishery products by using non-probability sampling technique to 142 consumers in three different locations in Pontianak (shops, mini/supermarkets, and local markets). Data were gathered by in-depth interviews divided into four categories consisting of consumer profiles; product knowledge; perception and preference; and quality dimension variable with conjoint analysis. The result shows that price, flavor, moistness, texture, nutrition, packaging color, and packaging size do not affect consumers’ decision to purchase the products. On the contrary, package durability attribute is the primary factor in their decision to purchase, and it is then followed by packaging material, availability, flavor, guarantee, guarantee source, brand, packaging form, and product form. This is beneficial for producers to improve the quality factors and develop market opportunities in the future. Besides, consumers can obtain information on product characteristics to fulfill their expectation and satisfaction.Keywords: conjoint analysis, fishery products, non-probability sampling, purchase behavior, quality dimensionsABSTRAKPeran produk olahan perikanan telah berkembang dan diakui dalam keamanan pangan–baik sebagai sumber pendapatan maupun sumber makanan bagi negara-negara berkembang. Namun, pengendalian terhadap karakteristik mutu menjadi sebuah tantangan dalam menghadapi keputusan pembelian konsumen. Tujuan penelitian adalah memahami dan mengevaluasi perilaku keputusan pembelian konsumen terkait dimensi mutu pada produk olahan perikanan menggunakan teknik non-probability sampling terhadap 142 konsumen pada tiga lokasi di Pontianak (toko, mini/supermarket, dan pasar lokal). Data dikumpulkan dengan metode wawancara mendalam yang terbagi menjadi empat bagian, yaitu profil konsumen; pengetahuan produk; persepsi dan preferensi; dan variabel dimensi mutu dengan conjoint analysis. Hasil menunjukkan bahwa harga, aroma, kelembaban, tekstur, nutrisi, warna kemasan, dan ukuran kemasan tidak memengaruhi keputusan pembelian konsumen. Namun, atribut daya tahan prduk menjadi faktor terpenting dalam keputusan pembelian yang diikuti dengan bahan kemasan, ketersediaan, aroma, jaminan, sumber jaminan, merek, entuk kemasan, dan bentuk produk. Hal tersebut bermanfaat bagi produsen untuk meningkatkan mutu yang dipentingkan oleh konsumen dan mengembangkan peluang pasar dimasa mendatang. Disamping itu, konsumen dapat memperoleh informasi karakteristik produk penting untuk memenuhi kepuasan dan harapan konsumen.Kata kunci: conjoint analysis, produk olahan perikanan, non-probability sampling, perilaku pembelian, dimensi mutu